Self-efficacy, self-esteem and engagement among Peruvian nurses during the COVID-19 pandemic - Ventura Egoávil, José (2023)
Introduction: Nursing professionals have faced the COVID-19 pandemic and health crisis on the front lines. Caught without technical and material readiness, as well as without previous experience, they resorted to using their own resources such as self-esteem and self-efficacy to raise their performance and uphold their commitment to public health. It has been reported that one third of the 37,000 nurses working in Peru contracted COVID-19, and approximately 180 died from the virus. Objectives: Measure the influence of personal resources on engagement among professional nurses during the COVID-19 pandemic. Methods: Cross-sectional explanatory correlational research from a sample of 387 Peruvian nursing professionals. A descriptive and inferential statistical analysis was performed. IBM SPSS Statistics V/26 software was used. Results: The results showed highly significant and positive correlations between the variables self-efficacy, self-esteem and engagement. Likewise, predictive values of more than 50% of personal resources on engagement were identified. Conclusions: Professional nurses during the pandemic perceived themselves with an average level of self-efficacy, high levels of self-esteem, and a medium level of engagement. Personal resources, self-efficacy and self-esteem, were able to predict the engagement of professional nurses in the dimensions of vigor, dedication and absorption.